Формування системи якості пасажирських перевезень - Єрмак, Олена (Видавництво Львівської політехніки, 2015)
The article identifies the factors affecting the quality of passenger transport. Describes the various methods used to assess the quality of urban passenger transport. Considered indicators that determine the level of quality of service. The theoretical aspects of management and quality assessment of passenger transportation made it possible to conclude that the diversity of existing approaches to assess this indicator. Passenger service quality depends on the organization of the transport process, design features and technical state of a used vehicle, route network development and other factors. Reliability and timeliness of the trip - one of the main criteria for assessing the quality of passenger service. Movement Scheduled passenger transport without disturbing regularity creates conditions guaranteed trip population over time. This increases the demand for transport, and increasing the efficiency of transport.
Formation of quality of passenger transportation